Entrepreneurial Engagement as a Catalyst for Human Empowerment: A Transdisciplinary Graduate Model (Lembaga Contrarius Indonesia, 2026)
This conceptual paper proposes a transdisciplinary framework to facilitate the transformation from knowledge to enterprise among social science and pure science graduates by positioning entrepreneurial engagement as a strategic pathway for human empowerment and progressive societal development. While grounded in the Malaysian higher education context, the framework is conceptualized to be adaptable across diverse national and institutional settings. Anchored in the Theory of Planned Behavior that explains how entrepreneurial intention and subsequent engagement are shaped by attitude, subjective norms, and perceived behavioral control. These psychological foundations are further strengthened through curriculum innovation, institutional support mechanisms, mentorship initiatives, and systematic exposure to entrepreneurial ecosystems. The framework responds to persistent global challenges surrounding graduate employability, skills mismatch, and the underutilization of scientific and social knowledge. By integrating transdisciplinary learning with established behavioral theory, the paper advances conceptual scholarship by extending the application of the Theory of Planned Behavior into a transdisciplinary entrepreneurial engagement domain. It highlights the importance of coordinated educational and institutional arrangements in nurturing empowered graduates capable of translating knowledge into meaningful enterprise. The paper concludes by outlining practical implications for higher education stakeholders and directions for future empirical validation.